Malignant Giant Cell Tumor in the Carpal Tunnel: A Case Report and Review of Literature - Theunissen, Carla I. J. M.; Bras, Johannes; Lienden, Krijn P. van; Obdeijn, Miryam C. (Journal of Wrist Surgery, 2013)
Background Malignant tenosynovial giant cell tumors (GCTs) are extremely rare, and their etiology is unknown. However, this type of malignancy is associated with high metastasis and mortality rates. Therefore, the treatment of choice is wide excision.Case Description A 66-year-old man complained of tingling and loss of sensation in the left hand, caused by a tumor that compressed the median nerve. The tumor was excised. Histopathologic examination revealed a ganglion cyst. Two years later, the patient visited our clinic with recurrent and similar complaints of the left hand. This time, however, the lesion turned out to be a malignant tenosynovial GCT and was treated by amputation of the forearm.Literature Review Since 1979, only 37 malignant tenosynovial GCTs have been reported in literature. Follow-up of these patients showed that 11 patients died of the disease, 4 patients were still living with the disease, and 14 patients had no evidence of disease after treatment. The other seven patients were lost to follow-up, and one patient died of other causes. In these 37 patients, a high incidence of lymph node metastasis (41%) and a high mortality rate (30%) were seen.Clinical Relevance Although this malignant tenosynovial GCT is very rare, high mortality rates have been observed because of the high incidence of lymph node metastases. Therefore, more awareness has to be created, to recognize and treat this tumor timely.
Keywords: malignant giant cell; carpal tunnel syndrome